Laser Surface Texturing for the Intensification of Boiling Heat Transfer in a Minichannel - Kinga Strąk; Magdalena Piasecka (Energies)
This study investigates the effects of using laser-textured surfaces in boiling heat transfer during cooling fluid flow in a minichannel. Several laser-textured surfaces, varied in roughness, were created on the heated plate surface that contacted FC-72 during flow in a single minichannel. Infrared thermography was used to measure temperature changes on the untextured side of the plate, while two-phase flow patterns were observed through a glass pane. Three vibration-assisted laser surface textures, previously investigated by the authors, and five novel laser surface textures were tested experimentally. The results were presented as relationships between heated wall temperature, heat transfer coefficient and distance along the minichannel, boiling curves, and flow patterns. The main interest of the authors was to provide a comparative analysis of the heat transfer results at the same value of heat flux supplied to the minichannel heated wall when either a laser-textured surface or a smooth base one was applied. It was noticed that the use of the 90-degree dense grid pattern type 2 (shallow) surface in the research helped achieve the highest local heat transfer coefficient in the subcooled boiling region compared to other surfaces tested. Furthermore, the 90-degree dense grid pattern type 1, characterised by larger maximum depth and height surfaces, performed best in the saturated boiling region. The results obtained for the laser-textured heated plate surface were compared to those collected for the smooth base heated plate surface, generally indicating an intensification of heat transfer processes in boiling heat transfer during FC-72 flow in a minichannel.